PENERAPAN ADAGIUM LEX SPECIALIS DEROGAT LEGI GENERALISS DALAM PENANGANAN TINDAK PIDANA KORUPSI DI INDONESIA - Zuliah, Azmiati; Amalia, Fitri (Universitas Dharmawangsa, 2025)
The crime of corruption is an extraordinary crime that has a broad impact on various aspects of life, including economic, social, and government. The principle of “Lex Specialis Derogat Legi Generalis” is the main basis in handling legal conflicts between general and specific provisions, especially in the context of law enforcement against corruption in Indonesia. Through Law Number 31 Year 1999 jo. Law Number 20 of 2001, this adage provides a more specific legal framework, enabling the application of more severe and effective sanctions against perpetrators of corruption.This research aims to analyze the application of the lex specialis principle in the eradication of corruption, including challenges such as overlapping norms, differences in interpretation, and systemic barriers. This research uses a normative juridical method with the approach of analyzing related legal documents. The results show that the application of the lex specialis principle provides clarity and efficiency in the law enforcement process, although it requires regulatory improvements and capacity building of legal apparatus. In conclusion, the application of this adage must continue to be refined through inter-agency collaboration, public education, and regulatory harmonization in order to create a fairer and more transparent legal system.